2014
DOI: 10.1016/s0959-8049(14)50601-6
|View full text |Cite
|
Sign up to set email alerts
|

682: Synergistic combination of valproic acid and oncolytic parvovirus H-1PV as a potential therapy against cervical and pancreatic carcinomas

Abstract: The rat parvovirus H-1PV has oncolytic and tumour-suppressive properties potentially exploitable in cancer therapy. This possibility is being explored and results are encouraging, but it is necessary to improve the oncotoxicity of the virus. Here we show that this can be achieved by co-treating cancer cells with H-1PV and histone deacetylase inhibitors (HDACIs) such as valproic acid (VPA). We demonstrate that these agents act synergistically to kill a range of human cervical carcinoma and pancreatic carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…In their experiment, mice received VPA at a dose of 100 mg•kg Ϫ1 •day Ϫ1 , whereas a dose of 200 mg•kg Ϫ1 •day Ϫ1 was used in our research, a dose that has been used in a previous report for renal carcinoma (29). In addition, studies have demonstrated that the dose of 200 mg/kg corresponds to the human equivalent of 32 mg/kg, which is below the 60 mg/kg limit considered safe and well tolerated in humans (4,34,43). Another difference between our research and the previous report was the duration of time in the experiments (9).…”
Section: Discussionmentioning
confidence: 99%
“…In their experiment, mice received VPA at a dose of 100 mg•kg Ϫ1 •day Ϫ1 , whereas a dose of 200 mg•kg Ϫ1 •day Ϫ1 was used in our research, a dose that has been used in a previous report for renal carcinoma (29). In addition, studies have demonstrated that the dose of 200 mg/kg corresponds to the human equivalent of 32 mg/kg, which is below the 60 mg/kg limit considered safe and well tolerated in humans (4,34,43). Another difference between our research and the previous report was the duration of time in the experiments (9).…”
Section: Discussionmentioning
confidence: 99%
“…Monotherapy of cancer often has limited success, as the tumor cells usually develop resistance to the agents used and tumors are usually genetically diverse (7,22). Therefore, it is important to identify combinations of two or more therapeutic agents, acting through different mechanisms with synergistic effects without increasing adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer targeting Gene-Viro-Therapy represents a promising approach for cancer therapy, which is designed through inserting an antitumor gene into an oncolytic viral vector that has the ability to selectively replicate in tumor cells but not in normal cells (4)(5)(6). More than 12 different oncolytic viruses are currently undergoing phase I-III clinical trials against various types of cancer (7). ZD55-TRAIL is an oncolytic adenovirus (OA) previously constructed in the laboratory of Xinyuan Institute of Medicine and Biotechnology at Zhejiang Sci-Tech University (Hangzhou, China), with the antitumor gene tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) inserted into the oncolytic vector ZD55 with E1B55-kDa deletion (8).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a reciprocal amplification of antitumoral effects was hypo thesized for putative HDACi plus OV combination regimens. In line with this, epi-virotherapeutic strategies already have proven to effectively boost tumor cell killing when compared with either monotherapeutic efficiencies (14,(18)(19)(20)(21)(22)(23), raising the novel term 'epi-viro therapeutic approach' (24).…”
Section: Introductionmentioning
confidence: 95%